SP22 sperm protein as a potential biomarker of fertility in humans: A preliminary study - Rosa, Josiane de Lima [UNESP]; Figueiredo, Thamiris Moreira [UNESP]; Barros, Jorge Willian Franco [UNESP]; dos Santos, Driéle Bretone [UNESP]; de Deus, Ramão Souza [UNESP]; Borges, Cibele Santos [UNESP]; Kempinas, Wilma De Grava [UNESP]; Klinefelter, Gary Robert (Elsevier, 2023)
Infertility affects approximately 15% of couples of reproductive age, and 50% of the cases are directly related to men. The evaluation of male fertility is based on analyses of routine seminal parameters and the use of more advanced techniques can help identify fertility biomarkers. SP22 sperm protein is considered a biomarker in murine species since its concentration is highly correlated with sperm fertility. As the role of this protein as a biomarker is already well-established in other species, we hypothesized that this same correlation could apply to human. Thus, the present study aimed to investigate possible correlations between SP22 concentration and sperm parameters in fertile and infertile men. For this, a study was carried out on 21 volunteers’ seminal samples who were grouped according to fertility as fertile (n = 10) or infertile (n = 11). Conventional and functional sperm analyses, membrane protein extraction, quantification and immunolocalization of SP22 were performed. The infertile volunteers showed an increase in the percentage of sperm with abnormalities in head morphology and a decrease in the percentage of sperm with intact plasma membrane and damaged acrosomal membrane. Serum concentration of the hormone SHBG was also decreased in infertile volunteers. The damage to the plasma membrane was positively correlated with the superoxide anion production. Although none of the functional parameters were correlated with SP22 concentration, type D sperm motility was negatively correlated and type A+B sperm motility was positively correlated. This preliminary study opens new paths in the characterization of SP22 as a non-invasive biomarker for predicting fertility/infertility.
Keywords: Fertility biomarker; Human sperm; Male infertility; Reproductive toxicity; SP22; Sperm protein